Conceptual Framework for the Mapping of Management Process with Information Technology in a Business Process - Vetrickarthick Rajarathinam; Swarnalatha Chellappa; Asha Nagarajan (The Scientific World Journal)
This study on component framework reveals the importance of management process and technology mapping in a business environment. We defined ERP as a software tool, which has to provide business solution but not necessarily an integration of all the departments. Any business process can be classified as management process, operational process and the supportive process. We have gone through entire management process and were enable to bring influencing components to be mapped with a technology for a business solution. Governance, strategic management, and decision making are thoroughly discussed and the need of mapping these components with the ERP is clearly explained. Also we suggest that implementation of this framework might reduce the ERP failures and especially the ERP misfit was completely rectified.